THE STUDY OF CHILDREN AND ADOLESCENTS MELATONIN SECRETION AFTER CRANIOPHARYNGIOMA REMOVING - E. Y. Iljina (Сеченовский вестник)
This article deals with the problem of children and adolescents melatonin secretion after removing the craniopharyngioma.